WANPRESTASI DALAM PERJANJIAN HUTANG PIUTANG PEMBERIAN PINJAMAN MODAL KERJA BERDASARKAN KITAB UNDANG-UNDANG HUKUM PERDATA (Studi Putusan M.A.R.I Nomor 1586K/Pdt/2020) - Norma Yunita, Ayu Herlin; Yasminingrum, Yasminingrum (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2025)
In practice, loan agreements involve borrowing and lending activities between individuals, typically with money as the object of the loan, and are established based on a contractual agreement. The provisions governing such agreements are stipulated in the Indonesian Civil Code, which sets out the rights and obligations of the parties involved. However, in practice, the legal relationship between creditors and debtors, particularly in contractual aspects, often encounters issues, leading to breaches of contract (wanprestasi). This study focuses on the legal consequences of wanprestasi in loan agreements, specifically in the context of working capital loans, and examines whether the relevant court decisions align with Article 1754 of the Indonesian Civil Code. This research employs a normative legal method, utilizing primary and secondary legal materials, which are subsequently analyzed through a descriptive-analytical approach. The findings conclude that money borrowed for business capital is based on a contractual agreement. The defendants were found to have breached the contract (wanprestasi) and are therefore obliged to repay the loan.